Peranan Program Yongjin Erp Sebagai Sistem Informasi Akuntansi Pengendalian Persediaan Bahan Baku - Humaeni, Anisa; Muanas, Muanas; Sudradjat, Sudradjat (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
Accounting information system provides information of raw material supplies and holds important roles for the company. Therefore, such activities need to carefully considered due to the elements of company’s assets possess material values in a relatively large amount, and are sensitive to subjects as time, damages, and unpredictable cost when wrongly managed. The purpose of this study is to investigate how far the application of accounting information system in Yongjin ERP manages the supplies data. This is what motivates the author to conduct a research on how the application of information accounting system can benefit in providing accurate information on raw material supplies required. In this study, the author used descriptive-qualitative method. The data used is of year 2017 obtained from the warehouse division. Data were collected through interviews and documentary studies. The study used two types of data sources, which are of primary and secondary. Overall data were obtained, collected, analyzed, and eventually interpreted to investigate the issue and seek for possible explanations. Yongjin Javasuka Company is a foreign owned company engage in manufacturing. The study concludes that the application of Yongjin ERP accounting information system, and the material module in particular have been put to good use and can be maintained further in the future. Likewise, a physical calculation is advisable to be executed more often, specifically on the warehouse division. This will guarantee accuracy of both physical and digital data.